Building Human Resources in Bioenergy: An International Training Program at Michigan State University - Callista Ransom; Karim Maredia (Journal of International Agricultural and Extension Education, 2012)
Biofuels and bioenergy has become a global issue due to the widespread interest in finding and developing alternatives to fossil fuels, including biofuels, while ensuring food security and environmental quality. Many developing countries have ample and unique bio-resources to utilize for generating bioenergy and have an opportunity to harness their rich biological resources. Education, capacity building, information, dialogue and networking are critical to better formulate appropriate policies, research, development, and outreach programs to address energy issues for sustainable development. Currently there is a lack of training programs, courses and curriculum devoted to biofuels/bioenergy.
Keywords: Bioenergy; Biofuels; Education; Training; Human Resources Development; Capacity Building; Professional Development